Playing with the Italian Renaissance : Assassin’s Creed players learning about Renaissance history through Ezio’s adventures - Giatsiou, Eftychia (fi=Turun yliopisto|en=University of Turku|, 2018)
This thesis studies the various methods through which Assassin’s Creed 2 and Brotherhood players learn about Renaissance Italy and what are the aspects in Renaissance history that they learn about. Through the narration of the story of a young Italian nobleman named Ezio Auditore da Firenze in Renaissance Italy, and how he endorsed the role of Assassin to avenge his family’s death, players engage with the Renaissance game world where Ezio’s story is actually narrated through Desmond Miles, a modern guy who enters a machine called animus that helps him travel back in Renaissance Italy and relive Ezio’s memories. The game designers at Ubisoft company have stayed true to the accurate representation of the past and how Italian Renaissance history is depicted in the games after thorough and extended research, so that players get the feeling that they travel back in the 15th-16th centuries through the gameplay. The methodological tools used for the analysis of my study derive from the fields of game studies, film studies, history, culture as well as the field of education. Many scholars have done research on the way video games can be effective learning tools for teaching certain materials like for instance history, and how they can be more engaging for the learners. Others have seen similarities in the way historical film and historical-based games represent the past. As a result, this thesis is supported by studies on historical film, historical-based games, narrative and education, providing valuable insight and comparisons for analysis. This thesis consists of four main chapters with the first one to analyze how Renaissance history is constructed in the AC games and how players engage with the learning of that history. The next chapter analyzes the methodology that has been used for conducting the research for this thesis and the steps that have been followed for interpreting the findings that derived from the data collection. The following chapter focuses on the analysis of the data collected from both the players’ and the development team’s participation in the survey. The chapter in particular analyzes the various methods through which the players learn about Renaissance Italy while playing, always in reference to the development team’s responses. The last chapter presents the aspects in Renaissance history about which the players learn and based on their responses focuses on three main aspects: historical characters, society and architecture. Finally, the chapter analyzes in depth some of the characteristics of each of the three categories depicted in the two games.